Influence of FMD vaccination stress on milk production in crossbred dairy cattle of Kerala - Venkatachalapathy, R Thirupathy; S, Pramod; Sahib, Lasna; Becha, Bibin (Indian Journal of Dairy Science, 2021)
Abstract Foot and mouth disease (FMD) is a contagious viral disease affecting cloven footed animals which is endemic in India. Primary disease control strategy in India is mass vaccination using oil adjuvant killed FMD vaccine containing O, A and Asia 1 serotypes. Variations in milk yield following vaccination with oil adjuvant killed FMD vaccine was studied in 80 crossbred cattle for a period of eight days. Rectal temperature and temperature humidity index (THI) were also monitored. Immunization using such vaccines resulted in transient febrile reaction and significant reduction in milk yield. Milk quality remained unaffected. Highest losses were observed on the first day after vaccination, which averaged at 0.58 Kg per animal. Total milk yield rebounded to pre vaccination levels by sixth day after vaccination. Average cumulative production loss calculated over the period was 1.93 Kg per animal. Notable changes in feed or water consumption were not observed. FMD vaccination, vaccination stress, milk production, production loss